Remittances and Macroeconomic Volatility in African Countries - Jidoud, Ahmat (Washington, D.C. : International Monetary Fund, 2015)
This paper investigates the channels through which remittances affect macroeconomic volatility in African countries using a dynamic stochastic general equilibrium (DSGE) model augmented with financial frictions. Empirical results indicate that remittances-as a share of GDP-have a significant smoothing impact on output volatility but their impact on consumption volatility is somewhat small. Furthermore, remittances are found to absorb a substantial amount of GDP shocks in these countries. An investigation of the theoretical channels shows that the stabilization impact of remittances essentially hinges on two channels: (i) the size of the negative wealth effect on labor supply induced by remittances and, (ii) the strength of financial frictions and the ability of remittances to alleviate these frictions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet